PENGARUH MOTIVASI DAN MODAL PSIKOLOGI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (Studi pada Dinas Kesehatan Kota Semarang) - Puguh Priyambodo, 12.5202.0209; Rijanti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the influence of motivation, psychological capital on job satisfaction, motivation, psychological capital and job satisfaction on employee performance motivation, psychological capital and job satisfaction on employee performance in Semarang City Health DepartemenÂ  mediated by job satisfaction. The total sample of 147 employees. Intake samples was done by the technique "pusrposive sampling".Testing using validity, reliability testing and regression testing. The research concludes motivation positive and significant effect on job satisfaction, psychological capital is able to provide a positive and significant effect on job satisfaction. Motivation is able to provide a positive and significant effect on performance. Psychological capital is able to provide a positive and significant influence on performance. Job Satisfaction is able to provide a positive and significant influence on performance. The test results indicate that job satisfaction is not a mediating variable Keywords : Motivation, Psyhcological Capital , Job Satisfaction and Peformance